(untitled) (Aporte Santiaguino, 2020)
The general objective of the studywas to evaluate the effects of topographic amplification of the soil due to the seismic response on the slopes of the Shancayán and Nueva Esperanza urbanizations of the city of Huaraz. The present investigation is of the quantitative and applied type, where the evaluation of the seismic response of the land in hillside areas that have unfavorable conditions for the foundation of the buildings has been carried out. The seismic response of the soil for an equivalent linear behavior applied to a geological-geotechnical model has been evaluated; performing a two-dimensional analysis, which models the stratigraphic profile of the terrain using the finite element method. The results of the seismic topographic amplification indicate that there are areas with a very high degree on slopes greater than 25° and areas with a high degree on slopes between 15° and 25°. The conclusion of the study indicates that the effects of seismic topographic amplification are considerable and increase at a greater slope of the terrain, and have a direct effect on the earthquake-resistant behavior of buildings.